2016
DOI: 10.1007/s13205-015-0321-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of molecular method for sex identification in date palm (Phoenix dactylifera L.) plantlets using novel sex-linked microsatellite markers

Abstract: Microsatellite markers containing simple sequence repeats (SSRs) are a valuable tool for genetic analysis. Date palm is a dioecious and slow flowering and is very difficult to identify the gender of the trees until it reaches the reproductive age (5–10 years). A total of 12 microsatellite primers were used with 30 date palm samples, 14 parents (8 male + 6 females) and 16 progeny (developed from parents breeding) which showed that microsatellites were highly polymorphic, having a great number of alleles. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…sharp point tips, curve and rough seeds in Figure 9 (Zango et al, 2016). This inventory was important because Elmer & Mattat (2012) could not investigate 117 female dates genetically and (Maryam 2016) postulated that we had to wait up to 5 years in order to find out a female date or when it produced fruits. This result showed that seedling date grew coiled roots at the 15 days old and produced circle leaf at the age of 30 days, so it did not need to wait until the first leaf emerged to find out that was a female date and this can safe time, energy and space for nursery.…”
Section: Female Date Investigationmentioning
confidence: 99%
“…sharp point tips, curve and rough seeds in Figure 9 (Zango et al, 2016). This inventory was important because Elmer & Mattat (2012) could not investigate 117 female dates genetically and (Maryam 2016) postulated that we had to wait up to 5 years in order to find out a female date or when it produced fruits. This result showed that seedling date grew coiled roots at the 15 days old and produced circle leaf at the age of 30 days, so it did not need to wait until the first leaf emerged to find out that was a female date and this can safe time, energy and space for nursery.…”
Section: Female Date Investigationmentioning
confidence: 99%
“…In contrast [35] amplified a band with RDA21 of size 900 bp. There is a huge difference in date palm cultivars grown under environmental conditions of Sudan [2]. Nevertheless each single primer from the four valid primers succeeded to amplify male specific fragments in all genotypes under study.…”
Section: Resultsmentioning
confidence: 98%
“…Introduction  Date palm (Phoenix dactylifera L) is diploid (2n=36), monocotyledonous plant [1], considers an important member of the family Arecaceae which contains 200 genera and 500 species [2]. It is native to North Africa and the Middle East and now distributed in Australia, India, Pakistan, Mexico, Southern Africa, South America, and the United States [3].…”
mentioning
confidence: 99%
“…Sex identification of date palm was subjected to a debate as newly developed sex-linked markers via DNA fingerprinting often failed when tested in other varieties or populations (Rania & Younis, 2008; Al-Mahmoud et al, 2012; Elmeer & Mattat, 2012; Dhawan et al, 2013; Maryam et al, 2016). Indeed, varieties of date palm germplasm and geographical populations were included as much when developing those markers, but the power of sex identification was limited by the variation of DNA sequences at the sex loci and, at that time, an unclear sex determination system in date palm.…”
Section: Discussionmentioning
confidence: 99%